The Sweet and Salty Dietary Face of Hypertension and Cardiovascular Disease in Lebanon - Labban, Mohammad M.; Itani, Maha M.; Maaliki, Dina; Radwan, Zeina; Nasreddine, Lara; Itani, Hana A. (Frontiers in Physiology, 2022)
According to the World Health Organization (WHO), an estimated 1.28 billion adults aged 30-79 years worldwide have hypertension; and every year, hypertension takes 7.6 million lives. High intakes of salt and sugar (mainly fructose from added sugars) have been linked to the etiology of hypertension, and this may be particularly true for countries undergoing the nutrition transition, such as Lebanon. Salt-induced hypertension and fructose-induced hypertension are manifested in different mechanisms, including Inflammation, aldosterone-mineralocorticoid receptor pathway, aldosterone independent mineralocorticoid receptor pathway, renin-angiotensin system, sympathetic nervous system activity, and genetic mechanisms. This review describes the evolution of hypertension and cardiovascular diseases (CVDs) in Lebanon and aims to elucidate potential mechanisms where salt and fructose work together to induce hypertension. These mechanisms increase salt absorption, decrease salt excretion, induce endogenous fructose production, activate fructose-insulin-salt interaction, and trigger oxidative stress, thus leading to hypertension. The review also provides an up-to-date appraisal of current intake levels of salt and fructose in Lebanon and their main food contributors. It identifies ongoing salt and sugar intake reduction strategies in Lebanon while acknowledging the country's limited scope of regulation and legislation. Finally, the review concludes with proposed public health strategies and suggestions for future research, which can reduce the intake levels of salt and fructose levels and contribute to curbing the CVD epidemic in the country.